Embedding MBA Students in Local Incubators and Accelerators. (July 2018) - Savoie, Matthew L.; Bendickson, Joshua S.; Edwards, Chase J.
This article presents an innovative method of engaging MBA students in a capstone course by offering a customizable project with businesses that are currently progressing through a regional, independent incubator, or accelerator program. We include various project options but focus on customizable capstone project alternatives to traditional business strategy simulations and case study methods. Namely, our innovative learning solution is a mock consulting project which drives innovation and fosters strategic collaboration between small business owners, university faculty, and MBA students while providing business strategy experience and generating positive exposure for both the university and the small businesses involved. Our method includes pairing MBA students with participating startup businesses and allowing the soon-to-be MBAs an opportunity to garner consulting experience while simultaneously serving the needs of the businesses in the accelerator. Accordingly, MBA students act as consultants to business owners and prepare detailed weekly briefings to inform stakeholders within the university and the constituent businesses. By breaching the typical capstone project parameters, the mock consulting option provides for experiential and applied learning experiences for MBA students and develops higher order strategic thinking by challenging them to work hand-in-hand with real startups.